Factors That Affect the Magnitude of Tibial Tubercle–Trochlear Groove Distance in Patients With Patellar Instability. Issue 1 (January 2023) - Hevesi, Mario; Dandu, Navya; Credille, Kevin; Wang, Zachary; Zavras, Athan G.; Cregar, William M.; Trasolini, Nicholas A.; Yanke, Adam B.
Background: Tibial tubercle–trochlear groove (TT-TG) distance is a risk factor for recurrent patellar dislocation and is often included in algorithmic treatment of instability. The underlying factors that determine TT-TG have yet to be clearly described in orthopaedic literature. Purpose/Hypothesis: The purpose of our study was to determine the underlying anatomic factors contributing to TT-TG distance. We hypothesized that degree of tubercle lateralization and knee rotation angle may substantially predict TT-TG. Study Design: Cross-sectional study; Level of evidence, 3. Methods: All patients evaluated for patellar instability at a single institution between 2013 and 2021 were included. Patients with previous knee osseous procedures were excluded. TT-TG and its anatomic relationship to patellofemoral measures, including dysplasia, femoral anteversion, tibial tubercle lateralization, knee rotation angle, and tibial torsion, were measured and subsequently quantified using univariate and multivariable analysis. Results: In total, 76 patients met the inclusion criteria (46 female, 30 male; mean ± SD age, 20.6 ± 8.6 years) and were evaluated. Mean TT-TG was 16.2 ± 5.4 mm. On univariate analysis, increasing knee rotation angle ( P < .01), tibial tubercle lateralization ( P = .02), and tibial torsion ( P = .01) were associated with increased TT-TG. In dysplastic cases, patients without medial hypoplasia (Dejour A or B) demonstrated significantly increased TT-TG (18.1 ± 5.4 mm) as compared with those with medial hypoplasia (Dejour C or D; TT-TG: 14.9 ± 5.2 mm; P = .02). Multivariable analysis revealed that increased knee rotation angle (+0.43-mm TT-TG per degree; P < .01) and tubercle lateralization (+0.19-mm TT-TG per percentage lateralization; P < .01) were statistically significant determinants of increased TT-TG distance. Upon accounting for these factors, tibial torsion, trochlear width, and medial hypoplasia were no longer significant components in predicting TT-TG ( P ≥ .54). Of note, all patients with TT-TG ≥20 mm had tibial tubercle lateralization ≥68%, a knee rotation angle ≥5.8°, or both factors concurrently. Conclusion: TT-TG distance is most influenced by knee rotation angle and tibial tubercle lateralization.